MODIFICATION OF NATURAL ZEOLITE AS MOLECULAR SIEVE MATERIAL ON BIOETHANOL DEHYDRATION - Khaidir Khaidir; Dwi Setyaningsih; Hery Haerudin (Jurnal Zeolit Indonesia, 2009)
This study aimed to find a method of modification zeolite structure so it has a fit pore size to used on bioethanol dehydration process and acquiring bioethanol quality for fuel. The method used by heating the mixture of ethanol azeotropic and water at distillation flask which passed through on the column filled by zeolite molecular sieve. The result showed that zeolite modifications (ZMS) have a better characteristic for used on bioethanol dehydration process than natural zeolite. The result which obtained on dehydration process using ZMS was better rather than commercial zeolite 3 A and natural zeolite. Concentration of bioethanol obtained by using ZMS has increased 3,14%.